Rhodosporidium toruloides and Tetradesmus obliquus Populations Dynamics in Symbiotic Cultures, Developed in Brewery Wastewater, for Lipid Production - Dias, Carla (2022)
ABSTRACT: In this work, primary brewery wastewater (PBWW) and secondary brewery wastewater (SBWW) separately, or mixed at the ratios of 1:1 (PBWW:SBWW) and 1:7 (PBWW:SBWW), with or without supplementation with sugarcane molasses (SCM), were used as culture media for lipid production by a mixed culture of the oleaginous yeast Rhodosporidium toruloides NCYC 921 and the microalgae Tetradesmus obliquus (ACOI 204/07). Flow cytometry was used to understand the dynamics of the two micro-organisms during the mixed cultures evolution, as well as to evaluate the physiological states of each microorganism, in order to assess the impact of the different brewery effluent media composition on the microbial consortium performance. Both brewery wastewaters (primary and secondary) without supplementation did not allow R. toruloides heterotrophic growth. Nevertheless, all brewery wastewater media, with and without SCM supplementation, allowed the microalgae growth, although the yeast was the dominant population. The maximum total biomass concentration of 2.17 g L-1 was achieved in the PBWW mixed cultivation with 10 g L-1 of SCM. The maximum lipid content (14.86% (w/w DCW)) was obtained for the mixed culture developed on SBWW supplemented with 10 g L-1 of SCM. This work demonstrated the potential of using brewery wastewater supplemented with SCM as a low-cost culture medium to grow R. toruloides and T. obliquus in a mixed culture for brewery wastewater treatment with concomitant lipid production.